Prevalence and antibiotic resistance in bacterial isolates of dogs with ulcerative keratitis in São Paulo State, Brazil - Casemiro, Pamella A. F. [UNESP]; Andrade, Alexandre L. [UNESP]; Cardozo, Marita V.; Rodrigues, Romario A. [UNESP]; Silva, Jaqueline A. [UNESP]; Marinho, Marcia [UNESP]; Nassar, Alessandra F. C.; Castro, Vanessa; Braz, Guilherme H. R.; Gujanwski, Cinthya A. [UNESP]; Padua, Ivan R. M. [UNESP]; Moraes, Paola C. [UNESP] (Wiley-Blackwell, 2024)
ObjectiveIdentify microorganisms present in canine eyes affected by ulcerative keratitis and assess its resistance profile to available antimicrobial drugs.MethodsSamples were collected from 88 canine eyes that exhibited ulcerative keratitis. They were identified using MALDI-TOF and subjected to antimicrobial susceptibility testing by disk diffusion.ResultsAmong the assessed subjects, brachycephalic dogs accounted for 74.48% (50/83) of the evaluated canines. Among the 88 evaluated eyes, 90.9% (80/88) showed positive cultures, with 11.33% (10/88) of the samples isolating more than one species of bacteria. Of all bacterial isolates identified (90), Gram-positive bacteria accounted for 63.33% (57/90), while Gram-negative bacteria constituted 36.66% (33/90), with predominance of Staphylococcus spp. at 35.55% (32/90) being, Staphylococcus pseudintermedius at 68.75% (22/32), and Pseudomonas aeruginosa at 15.55% (14/90), respectively. Staphylococcus spp. exhibited resistance to penicillin (89.29%), sulfadiazine and trimethoprim (60.71%), and tetracycline (67.86%), while doxycycline (88.89%), cefotaxime (85.71%), chloramphenicol (82.14%), gentamicin, and moxifloxacin (78.57%) showed the highest sensitivity rates. Pseudomonas aeruginosa displayed sensitivity (100%) to gentamicin and imipenem, and resistance (8.33%) to norfloxacin, ciprofloxacin, and cefepime. Similarly, the Enterobacteriaceae family showed higher sensitivity to amikacin and gentamicin (88.89%), imipenem (88.24%), and levofloxacin (87.5%), with pronounced resistance to amoxicillin-clavulanate (50%) and cefazolin (47.06%). This highlights multiresistance in 23.33% (21/90) of the isolates.ConclusionsThe most isolated species in canine ulcerative keratitis are S. pseudintermedius and P. aeruginosa. However, other species were also isolated, demonstrating diversity in ocular microbiota infection. There is a high-rate multidrug resistance associated with canine ulcerative keratitis. Nevertheless, these strains exhibited sensitivity to antimicrobials commonly used in veterinary ophthalmology.
Keywords: antimicrobials; cornea; dog; microorganisms; public health